A Quality Improvement Effort to Reduce Inpatient Opioid Consumption following Cesarean Delivery - McKenzie, Christine P.; Straube, Lacey; Webster, Carolyn; Cobb, Benjamin; Stuebe, Alison (American Journal of Perinatology, 2022)
Objective The amount of opioid prescribed following cesarean delivery (CD) is commonly in excess of patients' needs. An additional concern in a breastfeeding mother is neonatal opioid exposure. A maximum daily dose of 30 mg of oxycodone is recommended in breastfeeding women. Inadequate pain control can inhibit breastfeeding, as well as other negative consequences. We aimed to evaluate the effect of reducing the as-needed opioid ordered following CD on inpatient opioid consumption and analgesia.Study Design At our tertiary-care institution, our standard as-needed opioid order was reduced from oxycodone 5 to 10 mg every 4 hours to oxycodone 5 mg every 6 hours, in May 2019. Orders for scheduled acetaminophen and nonsteroidal anti-inflammatory drugs were unchanged. We compared opioid use and pain scores before (February 2019–April 2019) and after (May 2019–July 2019) the order modification. Our primary outcome was the proportion of patients using >30 mg of oxycodone in the 24 hours prior to hospital discharge. We further assessed 48-hour opioid consumption and patient-reported verbal pain scores.Results There were 559 patients who met inclusion criteria; 241 preintervention patients and 318 postintervention patients. In the preintervention group, 14.5% (35/241) used >30-mg oxycodone in the 24 hours before discharge, compared with 5.0% (16/318) after the order set change (relative risk [RR] = 0.34, 95% confidence interval [CI]: 0.19, 0.61; number needed to treat [NNT] = 10.5). There was no change in the proportion of women with one or more pain score >7 (preintervention: 44.4% [107/241], postintervention: 43.1% [137/318], p = 0.756) or >4 and ≤7 (preintervention: 36.9% [89/241], postintervention: 36.9% [125/318], p = 0.567), nor was there a change in mean pain score (mean ± standard deviation [SD]: preintervention = 2.8 ± 1.6 and postintervention = 2.7 ± 1.4, p = 0.464).Conclusion Reducing the amount of opioid ordered after CD reduced the proportion of post-CD patients exceeding the maximum recommended daily oxycodone dose for breastfeeding women.Key Points
Keywords: cesarean analgesia; multimodal analgesia; opioids and breastfeeding; opioid stewardship; oxycodone; pain; postpartum; postsurgical analgesia